Outsourcing of mutual funds' non-core competencies - Christoph Sorhage (University of Cologne, Centre for Financial Research (CFR), 2015)
Fund families strategically shape their member funds' behavior to target specific groups of investors with varying performance and service needs. In this paper I introduce a new measure to identify performance-oriented and service-oriented funds. Matching theories from the industrial organization literature, I suggest that funds whose families outsource the execution of services unrelated to portfolio management to external specialists are the same funds with an emphasis on their core business portfolio management. I find an outperformance of serviceoutsourced funds that is robust to a range of alternative explanations. Moreover, I show evidence that service-outsourced funds indeed possess superior investment skills.
Keywords: G23; L22; L84; 330; Mutual funds; Fund performance; Outsourcing; Shareholder services